2017
DOI: 10.1016/j.enganabound.2016.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Compact approximation stencils based on integrated flat radial basis functions

Abstract: This paper presents improved ways of constructing compact integrated radial basis function (CIRBF) stencils, based on extended precision, definite integrals, higher-order IRBFs and minimum number of derivative equations, to enhance their performance over large values of the RBF width. The proposed approaches are numerically verified through secondorder linear differential equations in one and two variables. Significant improvements in the matrix condition number, solution accuracy and convergence rate with gri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…However, the digits studied were 100-200, while the precise computation of the derivatives was vital for the extrapolation, and so for a higher number of digits. Similarly, Mai-Duy et al [52] examined the compactly integrated radial basis functions, with errors for the derivatives ε ~ O (10 −10 ) for fifty digits accuracy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the digits studied were 100-200, while the precise computation of the derivatives was vital for the extrapolation, and so for a higher number of digits. Similarly, Mai-Duy et al [52] examined the compactly integrated radial basis functions, with errors for the derivatives ε ~ O (10 −10 ) for fifty digits accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…The association of the condition number of Φ with ε ′ exhibits low R 2 (0.25595) with slightly negative slope (), although the high condition number is considered to increase instability [37, 41, 52] indicating the need for high precision to the calculations; however the majority of the values are 10 323 , that is, the maximum real number considered by the software [44]. Sensitivity analysis was selected instead of optimizing each method's parameters such as times of RBFs integration, the kernel function, or its shape parameter [4042], as the interpolation errors in a number of the test cases were equal to zero at the nodes, eliminating any relevant objective function.…”
Section: Discussionmentioning
confidence: 99%
“…One can bypass this issue by using extended precision in computation. In , numerical investigations indicated that the condition number of the conversion matrix grows much faster than that of the final system matrix. Here, we only use extended precision for constructing and inverting small conversion matrices (other computational parts including the solving of the final system of equations are conducted using double precision).…”
Section: Irbf Hermite‐based Method: Local Schemementioning
confidence: 99%
“…As β increases, the computed errors of the two methods fluctuate due to their higher matrix condition numbers. Several algorithms to extend the working range of the RBF width have been proposed in the literature (see, e.g., [15][16][17][18][19]37]). In this work, we use the extended precision approach.…”
Section: Odesmentioning
confidence: 99%
See 1 more Smart Citation